КОРИГУВАННЯ ЯКОСТІ СТРУМУ ЕЛЕКТРИЧНОЇ МЕРЕЖІ З ТИРИСТОРНИМ РЕГУЛЯТОРОМ ЗМІННОЇ НАПРУГИ НА АКТИВНО-ІНДУКТИВНОМУ НАВАНТАЖЕННІ - Чиженко, О.І.; Блінов, І.В. (Інститут електродинаміки Національної академії наук України, 2021)
The use of the AC voltage control method is considered. In this method, the improvement of the current quality of the supply network is achieved by a discrete change of the inductance in the network current flow circuit. In this method, it is proposed to use a circuit with counter-parallel thyristors and the neutral wire. The dependences of the harmonic coefficient and the current distortion coefficient of the electric network on the values of the regulated voltage are constructed. The obtained dependences prove the effectiveness of the proposed regulator. The required number of reactor sections is determined and the proper inductance of their windings to provide the values ​​of the harmonics coefficient that does not exceed 7% while adjusting the voltage depth of 50% on the active-inductive load. References 9, 3 figures 3, table.